2018
DOI: 10.31557/apjcp.2018.19.11.3153
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Epstein–Barr Virus Genotypes in Pakistani Lymphoma Patients

Abstract: The Epstein-Barr virus (EBV) is a herpesvirus infecting more than 90% of the human population. The tropism of EBV for B lymphocytes is evidenced in its association with many lymphoproliferative disorders. Different types of EBV (EBV-1 and EBV-2), classified on the basis of EBV nuclear antigen-2 (EBNA-2) genotyping, have been reported in benign and malignant pathologies, but there is almost no information about their frequency in the Pakistani population. The aim of this study was to determine the frequency and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
2
8
0
1
Order By: Relevance
“…Contrary to these findings, the majority of studies from other parts of the world showed a predominance of EBV type 1 in HL. Salahuddin et al (2018) showed the predominance of EBV type 1 in tissue samples in patients with various types of lymphoma from Pakistan (90.7%), similar to the results by Kafita et al (2018) obtained by analyzing biopsy samples from 150 cases of lymphoma (80% NHL, 20% HL) [ 34 , 35 ]. In Iran, Tabibzadeh et al (2021) showed a predominance of type 1 infections (91.2%) in the peripheral blood of 34 patients with various types of malignant diseases including 8 patients with HL [ 37 ] ( Table S3 ).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Contrary to these findings, the majority of studies from other parts of the world showed a predominance of EBV type 1 in HL. Salahuddin et al (2018) showed the predominance of EBV type 1 in tissue samples in patients with various types of lymphoma from Pakistan (90.7%), similar to the results by Kafita et al (2018) obtained by analyzing biopsy samples from 150 cases of lymphoma (80% NHL, 20% HL) [ 34 , 35 ]. In Iran, Tabibzadeh et al (2021) showed a predominance of type 1 infections (91.2%) in the peripheral blood of 34 patients with various types of malignant diseases including 8 patients with HL [ 37 ] ( Table S3 ).…”
Section: Discussionsupporting
confidence: 66%
“…In addition, an EBV molecular classification based on 12 EBV phylopopulations of monophyletic and paraphyletic origins that was obtained by using a Bayesian analysis of the population structure based on the alignments of masked genomes has also been described [ 15 ]. Multiple specific LMP1 variants have been described in benign and malignant EBV-associated diseases have been described but the data on their clinical relevance are still unclear [ 11 , 12 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. The aim of this study was to analyze the distribution of EBV genotypes 1 and 2 as well as EBV LMP1 variant diversity in patients with cHL from the Southeast of Europe in the context of clinical and pathological findings.…”
Section: Introductionmentioning
confidence: 99%
“…45 In a study conducted in Islamabad, the EBER-1 DNA, confirming EBV presence in tissue samples, was detected in 82% of the samples, thus implicating EBV in the aetiology of lymphoma, both Hodgkin’s and NHL, with the proportion detected increasing with the age of the patients (6–83 years). 46 For skin cancer including melanoma, exposure to ultraviolet radiation could induce a suppressed immune environment for the initiation of carcinogenesis using complex pathways. 47 However, this area is yet to be explored in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…According to our findings, only the type 1 genotype of EBV was prevalent in RA patients. A study performed in Pakistan on lymphoma patients detected both genotypes, with type 1 being most prevalent (90%) than type 2 (9%) [ 12 ]. Similarly, another study [ 23 ] observed 60% of type 1 and 26% of type 2 EBV genotypes in transgender sex workers in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies speculated that EBV infection is strongly associated with RA from different parts of the world [ 7 , 10 , 11 ]. In Pakistan, EBV has been detected in various lymphoma patients from different areas [ 12 14 ]. It is reported that RA is prevalent and increasing at a rate of 5.5% per year with a prevalence rate of 12.9–26.9% [ 15 ].…”
Section: Introductionmentioning
confidence: 99%